Facing Poetry Alexander Gottlieb Baumgarten's Theory of Literature - Berndt, Frauke (PARADIGMS, 2020)
What is Literature? According to Alexander Gottlieb Baumgarten, Literature is perfect sensate discourse. Based on this insight Baumgarten offers the first modern theory of literature. His uniquely holistic approach encompasses a methodology, epistemology, metaphysics, narratology, and ethics.